Wnt/β-catenin signaling is sufficient and necessary for synovial joint formation - Guo, Xizhi (Cold Spring Harbor Laboratory Press, 2004)
A critical step in skeletal morphogenesis is the formation of synovial joints, which define the relative size of discrete skeletal elements and are required for the mobility of vertebrates. We have found that several Wnt genes, including Wnt4, Wnt14, and Wnt16, were expressed in overlapping and complementary patterns in the developing synovial joints, where β-catenin protein levels and transcription activity were up-regulated. Removal of β-catenin early in mesenchymal progenitor cells promoted chondrocyte differentiation and blocked the activity of Wnt14 in joint formation. Ectopic expression of an activated form of β-catenin or Wnt14 in early differentiating chondrocytes induced ectopic joint formation both morphologically and molecularly. In contrast, genetic removal of β-catenin in chondrocytes led to joint fusion. These results demonstrate that the Wnt/β-catenin signaling pathway is necessary and sufficient to induce early steps of synovial joint formation. Wnt4, Wnt14, and Wnt16 may play redundant roles in synovial joint induction by signaling through the β-catenin-mediated canonical Wnt pathway.